Designing transformative service initiatives (TSIs) in polarised contexts : a framework for effective practice - Russell-Bennett, Rebekah; Gasparin, Isadora; Gnusowski, Marek; Vredenburg, Jessica; Ahmed, Junaid; Ercan, Selen (Emerald, 2026)
Purpose
Transformative service initiatives (TSIs) are often applied to address wicked problems in contexts that are polarised. For TSIs to be effective, they require both diversity of perspectives, a level of social cohesion and acceptance of the TSI as legitimate. Yet polarisation typically undermines cohesion and fuels resistance within communities, limiting the effectiveness of TSIs. The purpose of this study is to address the problem of how to manage diversity of perspectives when designing TSIs in a polarised context.
Design/methodology/approach
The authors adopt a theory synthesis approach and combine insights from service design with the theory and practice of deliberative democracy. The authors draw on deliberative democracy, as it offers practical tools and strategies for addressing disagreements in polarised contexts. The study brings together two distinct literature streams into a single conceptual theme to develop a framework for effective TSI design in polarised contexts.
Findings
In polarised contexts, the effective design and delivery of TSIs requires close attention to three features: actors (who should participate in the process, what types of citizens have an interest in the topic and what perspectives are represented); processes and practices (how the initiative is structured and what behaviours can be enabled to address polarisation); and outcomes (what can the process realistically yield, recognising that consensus may not always be possible).
Originality/value
To the best of the authors’ knowledge, the research is the first to introduce deliberative democracy theory to the services marketing literature. The core contribution of the proposed framework is the identification of bridging and bonding practices as the key mechanisms for creating procedural legitimacy of a TSI in a polarised context.